2016
DOI: 10.1038/srep30711
|View full text |Cite
|
Sign up to set email alerts
|

Olig2 regulates Purkinje cell generation in the early developing mouse cerebellum

Abstract: The oligodendrocyte transcription factor Olig2 plays a crucial role in the neurogenesis of both spinal cord and brain. In the cerebellum, deletion of both Olig2 and Olig1 results in impaired genesis of Purkinje cells (PCs) and Pax2+ interneurons. Here, we perform an independent study to show that Olig2 protein is transiently expressed in the cerebellar ventricular zone (VZ) during a period when PCs are specified. Further analyses demonstrate that Olig2 is expressed in both cerebellar VZ progenitors and early-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 42 publications
7
56
2
Order By: Relevance
“…1C,C′). A subset of ZFP423 PC progenitors also expresses the marker OLIG2, which is mostly associated with G0/G1 PC progenitors (Ju et al, 2016). Likewise, the domain containing differentiating PC precursors positive for CORL2 colocalizes Fig.…”
Section: Resultsmentioning
confidence: 91%
“…1C,C′). A subset of ZFP423 PC progenitors also expresses the marker OLIG2, which is mostly associated with G0/G1 PC progenitors (Ju et al, 2016). Likewise, the domain containing differentiating PC precursors positive for CORL2 colocalizes Fig.…”
Section: Resultsmentioning
confidence: 91%
“…On day 35, cells were already positive for OLIG2, CORL2, and BARHL1. OLIG2 is the earliest marker for Purkinje cells, and is associated with cell cycle exit and differentiation into postmitotic neurons (Takebayashi et al, 2002;Seto et al, 2014;Ju et al, 2016). CORL2 is specifically expressed in post-mitotic Purkinje cell precursors shortly after exiting the cell cycle (Minaki et al, 2008) and plays an essential role in Purkinje cell development (Wang et al, 2011;Nakatani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Basally located cells further expressed PAX2 (Figures 2I,I' and Supplementary Figure S3F), which is a marker of GABAergic interneurons and their precursors in the developing cerebellum (Zhang and Goldman, 1996;Maricich and Herrup, 1999). Cells positive for OLIG2, a transcription factor expressed in neurogenic progenitors and nascent Purkinje cells (Seto et al, 2014;Ju et al, 2016), were also predominantly located in the basal layer ( Figures 2J,J' and Supplementary Figures S3G,G').…”
Section: Cerebellar Progenitors In 3d Culture Self-organize Into Polamentioning
confidence: 99%
“…Lineage tracing suggested that other types of GABAergic VZ precursors also derive from Sox2 + eCSCs. We examined the expression of other VZ precursor markers, namely Olig2, which maintains the identity of PC progenitors 16 , and Lhx1/5, a marker for early GABAergic cells, in Psn KO mice and found that both were decreased, concomitantly with the increase in the number of Atoh1 + cells (Fig. S7C and S7D-H).…”
Section: Body Textmentioning
confidence: 99%